2018
DOI: 10.1016/j.ijrmms.2018.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Wellbore breakout prediction in transversely isotropic rocks using true-triaxial failure criteria

Abstract: This paper presents a unified approach through which the influence of the elastic and strength anisotropy on wellbore instability can be thoroughly examined. The stresses at the wellbore wall are first calculated using the Lekhnitskii-Amadei solution, which accounts for elastic anisotropy. Then, shear failure is treated by combining the Mogi-Coulomb criterion for intact rock, with the Jaeger plane of weakness concept. The developed model accounts for all three principal stresses in predicting the onset of shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Although not universal, one recurring theme that appears in many of the above studies is that BO azimuths often change along a given borehole. Even though the underlying assumptions employing the equations are widely used in the literature, it has long been known that the drilling induced failure pattern may not reflect true far-field stresses and is complicated by deviations of the borehole from a principal stress direction (Mastin, 1988), geological discontinuities (Lin et al, 2007;Sahara et al, 2014;Shamir & Zoback, 1992;Yale, 2003;Zakharova & Goldberg, 2014), contrasting mechanical properties in different lithology (Agheshlui & Matthai, 2017;Pham et al, 2020), and rock strength anisotropy in the layered sediment or foliated crystalline basement (Setiawan & Zimmerman, 2018;Vernik & Zoback, 1989;. Analyses based on the equations have led to interpretations of variable stress states between the sediment and basement, such as a ~30° change in the SH orientation in Basel and Rittershoffen , and a stress state change from normal faulting stress regime in the sediment to strike/thrust faulting stress regime in the basement in Songliao Basin, China (B.…”
Section: Prior Studies Of Crustal Stress In Cratons and Other Crystal...mentioning
confidence: 99%
“…Although not universal, one recurring theme that appears in many of the above studies is that BO azimuths often change along a given borehole. Even though the underlying assumptions employing the equations are widely used in the literature, it has long been known that the drilling induced failure pattern may not reflect true far-field stresses and is complicated by deviations of the borehole from a principal stress direction (Mastin, 1988), geological discontinuities (Lin et al, 2007;Sahara et al, 2014;Shamir & Zoback, 1992;Yale, 2003;Zakharova & Goldberg, 2014), contrasting mechanical properties in different lithology (Agheshlui & Matthai, 2017;Pham et al, 2020), and rock strength anisotropy in the layered sediment or foliated crystalline basement (Setiawan & Zimmerman, 2018;Vernik & Zoback, 1989;. Analyses based on the equations have led to interpretations of variable stress states between the sediment and basement, such as a ~30° change in the SH orientation in Basel and Rittershoffen , and a stress state change from normal faulting stress regime in the sediment to strike/thrust faulting stress regime in the basement in Songliao Basin, China (B.…”
Section: Prior Studies Of Crustal Stress In Cratons and Other Crystal...mentioning
confidence: 99%
“…Setiawan [23] introduced a new complex variable function on complex variables, which was expressed as Eq. 8:…”
Section: Wellbore Stabilization Model For Anisotropic Formationmentioning
confidence: 99%
“…Therefore, it is determined that the direction of the weak plane is closely related to wellbore failure [22]. As a result, the isotropic wellbore stress distribution model is established [23,24], and it is found that Poisson's ratio has little influence on borehole stability in shale formation [25,26]. However, these studies often adopt assumed values, or only give experimental results, for the anisotropy of shale strength.…”
Section: Introductionmentioning
confidence: 99%
“…One recurring theme appearing in the above studies is that BO azimuths often change along a given borehole. Even though the 2D Kirsch (1898) equations are widely employed, it has long been known that BOs and DITFs are complicated by deviations of the borehole from a principal stress direction (Mastin, 1988), geological discontinuities (Day‐Lewis et al., 2010; Lin et al., 2007; Sahara et al., 2014; Shamir & Zoback, 1992; Yale, 2003; Zakharova & Goldberg, 2014), contrasting mechanical properties in different lithology (Agheshlui & Matthai, 2017; Pham et al., 2020), and rock strength anisotropy in the layered sediment or foliated crystalline basement (Setiawan & Zimmerman, 2018; Vernik & Zoback, 1989; W. Wang et al., 2022). Analyses based on Kirsch (1898) equations have led to interpretations of variable stress states between the sediment and basement, such as a ∼30° change in the S H orientation in Basel and Rittershoffen (Azzola et al., 2019) and a change in the stress state from a normal faulting stress regime in the sediment to a strike/thrust faulting stress regime in the basement in Songliao Basin, China (B. Wang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%